Improving the Performance and Finding Bitmap of the Compression Method Using Weber’s law - Hameed, Maha A.; Mahdi, Dhiaa (Iraqi Journal of Science, 2025)
Image compression is a suitable technique to reduce the storage space of an image, increase the area of storage in the device, and speed up the transmission process. In this paper, a new idea for image compression is proposed to improve the performance of the Absolute Moment Block Truncation Coding (AMBTC) method depending on Weber’s law condition to distinguish uniform blocks (i.e., low and constant details blocks) from non-uniform blocks in original images. Then, all elements in the bitmap of each uniform block are represented by zero. After that, the lossless method, which is Run Length method, is used for compressing the bits more, which represent the bitmap of these uniform blocks. Via this simple idea, the result is improving the compression for the bitmap’s size by reducing it, then reducing the bit rate further with a high ratio in compression and high speeding in the transition or storage while also retaining the reconstructed image quality.